1963
DOI: 10.1136/jcp.16.4.319
|View full text |Cite
|
Sign up to set email alerts
|

A cytological and histological study of acute premyelocytic leukaemia

Abstract: SYNOPSIS Among the acute leukaemias of the granulocytic group, acute premyelocytic leukaemia is distinguished by the severity of its haemorrhages, the frequency of hypofibrinaemia, a rapidly fatal course, and an unusual cellular hyperplasia. Myelograms show an increased proportion (average 80%) of characteristic cells of large diameter, with numerous azurophil granules. The infiltration of other organs is inconstant. MATERIAL AND METHODS Acute premyelocytic leukaemia represents about 6-8 % of all cases of acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

1969
1969
1997
1997

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Although there have been several case reports, its incidence is somewhat uncertain in the absence of cytogenetic and/or molecular confirmation of the diagnosis in many earlier studies. For example, Bernard et al (1963) reported two cases of CNS relapse amongst 25 patients with morphological APL. More recent larger studies, which also predate the advent of the widespread use of ATRA, such as the UK MRC AML X Trial, have established the rarity of CNS relapse in patients with a clinical diagnosis of APL.…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been several case reports, its incidence is somewhat uncertain in the absence of cytogenetic and/or molecular confirmation of the diagnosis in many earlier studies. For example, Bernard et al (1963) reported two cases of CNS relapse amongst 25 patients with morphological APL. More recent larger studies, which also predate the advent of the widespread use of ATRA, such as the UK MRC AML X Trial, have established the rarity of CNS relapse in patients with a clinical diagnosis of APL.…”
Section: Discussionmentioning
confidence: 99%
“…The char acteristic giant granules seen have cytochemical and ultrastructural similarities with the inclusion bodies of the CHS [5,6,9,16,25,34], We can surmise whether there is any re lation between the absence of biologic symptoms of DIC in our case report and the absence of any crystalline structure in abnormal granules and ABs. In fact, several workers have reported that the DIC is closely associated with the abund ance of intracellular ABs [4,11,15,27]. On the other hand, many ultrastructural stud ies have demonstrated a periodicity and crystalline structure in ABs [5,7], Tulliez and Breton-Gorius [31] suggested that the DIC was associated with the pres ence of types I and 111 ABs related to some crystallized proteins that may act upon coagulation.…”
Section: Discussionmentioning
confidence: 99%
“…MSV-MLV virus was obtained from the supernatant fluids of a chronically infected line (78Al cell line) [6]. It was labeled and purified as described elsewhere [7] .…”
Section: Obtention Of Viral Rnamentioning
confidence: 99%